Increased concentrations of bovine intestinal mucus encourage growth of Escherichia coli O157:H7 - Heidenreich, J.; Aperce, C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Cattle have been implicated as carriers of the human pathogen Escherichia coli O157:H7. Contamination of the beef supply by E. coli O157 can occur during harvest and processing, causing costly recalls or human illness. Many interventions have been applied in attempts to prevent contamination of carcasses in processing plants, such as development of HACCP procedures, carcass washes, and steam pasteurization, but contaminations still occur. Mechanisms that allow E. coli O157:H7 to thrive in cattle at sporadic times and in such large numbers are poorly understood. Understanding factors that stimulate E. coli O157 growth in cattle will aid in identifying effective interventions that can be applied in feedlots and processing plants to reduce the numbers of this pathogen. E. coli O157 resides in the intestinal tracts of cattle. Mucin is a major component of intestinal mucus and is composed of proteins, lipids, and carbohydrates, which many bacteria can use as a source of food. The amount of mucin available in the intestinal tract depends on the stimulation of intestinal mucus-producing cells (goblet cells), which may be influenced by the animal’s diet, stress, and a variety of other factors. Our objective in this experiment was to determine if mucin produced in the small or large intestine could affect growth of E. coli O157:H7.
Keywords: Beef; Intestinal mucus; Escherichia coli; Bacteria